Examining the robustness of selected microalgae to grow in landfill leachate - Nugroho, Wahyunanto Agung; Hj Hassan, Ummul Hasanah (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Microalgae is widely recognized as a leading candidate for future bio-oil production, serving dual purposes: biodiesel generation and bioremediation. Identifying a sustainable cultivation medium is essential, aiming to minimize production costs. Landfill leachate emerges as a prospective growth medium for microalgae. However, due to the diverse substances within landfill leachate that may impede microalgal growth, careful selection of robust species becomes crucial. This study examined the growth of four microalgae species—Chlamydomonas reindhartii, Chlorella vulgaris, Chlorella ovalis, and Nannochloropsis oculata—in landfill leachate. Prior to utilization, the landfill leachate underwent treatment to remove the total ammonium nitrogen (TAN). Cultivation spanned 30 days, during which various parameters, including ammonium removal, growth rate, and oil content, were monitored. Initially, all microalgae exhibited a decline in numbers, succeeded by a subsequent increase in concentration after several days. Results revealed Nannochloropsis oculata to have the highest growth rate, while Chlamydomonas reindhartii displayed the lowest. Generally, the oil content of all species at the end of cultivation was lower than that of their respective inocula. Chlorella vulgaris exhibited the highest oil content, followed by Chlamydomonas reindhartii, Chlorella ovalis, and Nannochloropsis oculata.